Right Hemisphere Involvement in Non-Fluent Primary Progressive Aphasia - Claudia Repetto; Rosa Manenti; Maria Cotelli; Marco Calabria; Orazio Zanetti; Barbara Borroni; Alessandro Padovani; Carlo Miniussi (Behavioural Neurology)
We described a 56-years-old man with a diagnosis of “non-fluent primary progressive aphasia” (NfPPA). An accurate neuropsychological, neurological and neuroimaging evaluation was performed in order to assess clinical and behavioural features of the patient.